Metformin Protects Against Sunitinib-induced Cardiotoxicity: Investigating the Role of AMPK. Issue 6 (June 2022) - Kuburas, Refik; Gharanei, Mayel; Haussmann, Irmgard; Maddock, Helen; Sandhu, Hardip
Abstract: Sunitinib is associated with cardiotoxicity through inhibition of AMP-protein kinase (AMPK) signaling. By contrast, the common antidiabetic agent metformin has demonstrated cardioprotection through indirect AMPK activation. In this study, we investigate the effects of metformin during sunitinib-induced cytotoxicity. Left ventricular developed pressure, coronary flow, heart rate, and infarct size were measured in Langendorff-perfused rat hearts treated with 1 µM sunitinib ±50 µM metformin ±1 µM human equilibrative nucleoside transporter inhibitor S-(4-Nitrobenzyl)-6-thioinosine (NBTI). Western blot analysis was performed for p-AMPKα levels. Primary isolated cardiac myocytes from the left ventricular tissue were used to measure live cell population levels. 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay was used to assess adjunctive treatment of and metformin in human hepatoma G2 and promyelocytic leukemia (HL-60) cells treated with 0.1–100 µM sunitinib ±50 µM metformin. In the perfused hearts, coadministration of metformin attenuated the sunitinib-induced changes to left ventricular developed pressure, infarct size, and cardiac myocyte population. Western blot analysis revealed a significant decrease in p-AMPKα during sunitinib treatment, which was attenuated after coadministration with metformin. All metformin-induced effects were attenuated, and NBTI was coadministered. The MTT assay demonstrated an increase in the EC50 value during coadministration of metformin with sunitinib compared with sunitinib monotherapy in hepatoma G2 and HL-60 cell lines, demonstrating the impact and complexity of metformin coadministration and the possible role of AMPK signaling. This study highlights the novel cardioprotective properties of metformin and AMPK activation during sunitinib-induced cardiotoxicity when administered together in the Langendorff heart model.